MEHDI HAIRI YAZDI’S ‘ILM ḤUḌŪRĪ: A RESPONSE TO CONTEMPORARY EPISTEMOLOGICAL DEBATES - Farkhan Fuady; Zainun Kamaluddin Fakih; Kholid Al Walid; Yusuf Rahman (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2025)
This article aims to analyze Mehdi Hairi Yazdi’s contribution in responding to contemporary epistemological contestation through the idea of ‘ilm ḥuḍūrī. The main problem in modern epistemology lies in the relationship between the subject and object of knowledge, which tends to be dualistic in the Western epistemological tradition. Hairi Yazdi offers ‘ilm ḥuḍūrī as an alternative solution in modern epistemology. This research is a literature study using a qualitative method, and its data sources are from Mehdi Hairi Yazdi’s works and relevant research. The research findings show that Hairi Yazdi’s idea of ‘ilm ḥuḍūrī cannot only bridge the gap between rationalism and empiricism but provide a strong epistemological basis for the validity of mystical experiences. Furthermore, this idea offers a new perspective in studying Islamic philosophy. It contributes to the development of inclusive knowledge in facing the challenges of contemporary epistemology. Thus, this study emphasizes the importance of ‘ilm ḥuḍūrī as an alternative paradigm that enriches contemporary epistemological discourse.